Emojis as Communication Medium Among College Students in a State-Run Institution - Aranas, Kylie Kate S.; Marte, Marifel B.; Valentin, Christian Jay S.; Biray, Ersyl T. (Future Science / FSH-PH Publications, 2024)
Emojis are small images conveying meaning, emotions, and tone embedded in electronic text messages that allow people to express their feelings and emotions in nonverbal and informal conversations. This study aimed to find out the role of emojis as a communication medium among college students in a state-run institution. Specifically, it sought to identify the popularly-used emojis, the social media platforms where these are used, determine their frequency of use, and the instances where these are used. Sophomore college students enrolled in a teacher education degree program specializing in the English language at a state-run university supplied the data collected using a validated survey questionnaire transformed and sent through the Google messenger application. Results revealed that the topmost popular emojis used by college students in their nonverbal communication were the heart, face with tears of joy, and loudly crying face. Participants stated that they always use emojis in their informal communication with friends on popular social media platforms, such as Facebook and Messenger. It was also established that emojis were used when messaging friends or family members expressing their feelings, and having nothing else to reply to in a conversation. These findings attest that the use of technology-driven trends has evolved in the communication media, particularly among the younger generation.